Importance of the Study of the Right Heart Chambers in Symptomatic Acute Pulmonary Embolism - Nuria Rodríguez‐Núñez; Alejandra Virgós‐Pedreira; Alfonso Illade‐Fornos; Lucía Ferreiro‐ Fernández; María E. Toubes‐Navarro; Luis Valdés‐Cuadrado (Respirology Case Reports)
ABSTRACT We present the case of a 42‐year‐old woman on oral contraceptives that presented to the emergency department with pain and swelling in the left lower limb. Diagnosis of extensive deep vein thrombosis was established. A few minutes later, she exhibited signs of shock and hemodynamic instability, thus raising suspicion of high‐risk acute pulmonary thromboembolism. Prior to the administration of fibrinolytic treatment, a bedside transthoracic echocardiography was performed that excluded right ventricular dilatation. Then, the study was complemented with a thoraco‐abdominal computed tomography scan that demonstrated a large retroperitoneal hematoma as the cause of the shock. In conclusion, a transthoracic echocardiography should be performed before initiating thrombolytic therapy in hemodynamically instable patients with strong suspicion of high‐risk pulmonary embolism.